PENINGKATAN KESEJAHTERAAN EKONOMI DENGAN MENUMBUHKAN JIWA DAN SEMANGAT KEWIRAUSAHAAN - Tanuwijaya, Justine; Magetsari, Ovy Noviati Nuraini; Leon, Farah Margaretha; Derita, Anastasia Mariana; Iskandar, James (Jurnal Pengabdian dan Kewirausahaan, 2024)
After the Covid-19 pandemic, it still has the impact of limited job opportunities, and quite a number of companies have even been forced to lay off some active employees. One alternative solution is entrepreneurship. This condition is the background for community service activities (PKM) taking topics related to the soul and spirit of entrepreneurship, which is a need for the residents assisted by PSBR Taruna Jaya 1,aged 16 - 22 years, who are the young generation of Indonesia who must be trained as well as possible,  by utilizing creativity and high enthusiasm. PSBR TJ 1 is the Technical Implementation Unit (UPT) of the Social Service in the Development of Youth with Social Problems, both out of school and neglected teenagers in the DKI Jakarta Province environment. PKM activities were carried out on January 12 2024 face to face at the PSBR TJ 1 location with a total of 55 participants. During the process of delivering the material, the activity ran well and smoothly. The participants were enthusiastically involved in questions and answers and discussions. The method used is counseling. The participants considered the topic presented to be very relevant to their needs. Furthermore, the Head of PSBR Taruna Jaya 1 who was present and gave opening remarks at this activity hoped that similar activities could be carried out at a later date with a longer duration of counseling time. In the future, PSBR TJ 1 can be built by the Faculty of Economics and Business, Universitas Trisakti